Using Input-Output Analysis to Measure Healthy, Sustainable Food Systems - Boylan, Sinead M.; Thow, Anne-Marie; Tyedmers, Elijah K.; Malik, Arunima; Salem, Janet; Alders, Robyn; Raubenheimer, David; Lenzen, Manfred (Frontiers in Sustainable Food Systems, 2020)
Our current food systems are hampering efforts to meet the Sustainable Development Goals. Reshaping our food systems could have enormous co-benefits for our populations and planet. However, decision makers and experts are questioning whether it is possible to meet environmental, social and economic goals simultaneously, or whether tradeoffs are necessary. There has been a call for the development of better measurements and indicators to help policymakers understand the benefits and considerations for healthy and sustainable food systems. There is an urgent need to address the gaps in understanding of what a sustainable food system means across varying populations and geographies and how we can better measure these systems. Practice calls for a framework in which different aspects of food and nutrition security can be measured under identical scope, where policy simulations which arrive at multi-indicator outcomes are comparable, and where quantified trade-offs between different sustainable development objectives are valid. We introduce, and focus on one technique that does allow such multi-indicator scope-consistent analysis of food systems under a life-cycle perspective: input-output analysis. We describe input-output analysis, and its relevance and advantages for measuring the sustainability of food systems, nutrition and diets, including resilience and vulnerability. Using data from the global multi-regional input-output databases, we then describe potential measures that are able to extend the current state of art into a more comprehensive framework that has the potential to support policy related to global initiatives such as the Sustainable Development Goals.